Study on Attribution Analysis and Response of Saltwater Intrusion in Modaomen Waterway During Dry Seasons - HUANG Chunhua; LIN Zhongyuan; ZOU Huazhi; HUANG Pengfei; XU Wei (Renmin Zhujiang)
Under the influence of climate change and human activities, the saltwater intrusion in the Modaomen Estuary Waterway has intensified significantly,which has greatly threatened the safety of the water supply in the Guangdong-Hong Kong-Macao Greater Bay Area.Based on the daily exceedance time data of seven stations in the Modaomen Waterway,daily maximum tidal range,volume of runoff, mean sea level,cross-shore wind,and alongshore wind from 2004 to 2016,empirical orthogonal function (EOF) analysis and univariate and multiple linear regression analysis were carried out to reveal the response relationship between the saltwater intrusion and the impact factors and quantify the contribution of each impact factor.The results show that the maximum contribution to the saltwater intrusion is the tidal range,followed by the volume of runoff, which can explain 30% and 28% of the diurnal variation of the exceedance time, respectively.The contribution of wind to the saltwater intrusion is slightly greater than that of the mean sea level,and the contribution of wind and mean sea level to the saltwater intrusion is 12% and 11%,respectively.The effect of cross-shore wind is slightly greater than that of alongshore wind.The peak of Modaomen saltwater intrusion appears in 3.2 days after the minimum tidal range,and the salinity of Modaomen Waterway is not suppressed until 1.8 days after the increase in the volume of runoff of Gaoyao station.This paper can provide theoretical support for watershed scheduling and saltwater intrusion forecast.